A Comparative Semiotic Analysis of Pocari Sweat Advertisements in Ramadan and Sports Context Based on Peirce’s Theory - Ruthertati Sianturi; Muhammad Abiyyu De Rossi; Monika Br. Tobing; Syifa Inayah Hanani Zulfa; Pegrina Yuni Permatasari Siregar; Meisuri Meisuri (Asosiasi Periset Bahasa Sastra Indonesia, 2026)
This study examines how meaning is constructed in two Pocari Sweat advertisements presented in different contexts, namely Ramadan (sahur) and sports, using Charles Sanders Peirce’s semiotic theory. Advertising today not only promotes products but also communicates cultural values and social meanings through signs such as images, language, and symbols. The objective of this research is to identify the types of signs used, interpret their meanings, and compare how different contexts influence meaning construction. This study applies a qualitative descriptive method by analyzing visual and verbal elements from both advertisements. The findings show that both advertisements use icons, indexes, and symbols, but with different emphases. The Ramadan advertisement highlights symbolic and cultural meanings related to togetherness, spirituality, and health during fasting, while the sports advertisement emphasizes physical activity, endurance, and performance through more indexical and iconic signs. These differences indicate that advertising strategies adapt to audience context to create specific interpretations. The study implies that advertisements function as complex systems of meaning that shape audience perception, and understanding these signs can help viewers become more critical in interpreting media messages.